2002
DOI: 10.2460/javma.2002.220.1315
|View full text |Cite
|
Sign up to set email alerts
|

Effects of diet restriction on life span and age-related changes in dogs

Abstract: Results suggest that 25% restriction in food intake increased median life span and delayed the onset of signs of chronic disease in these dogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
390
1
13

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 498 publications
(433 citation statements)
references
References 15 publications
14
390
1
13
Order By: Relevance
“…This damage is thought to remain latent for some time, but eventually results in an earlier onset of aging and degenerative disease as well as increased rates of certain cancers. This theory is supported by the finding that adult giant breed dog cells have a lower proliferative capacity than those of other breeds (45), that large dogs tend to develop nonhereditary cataracts (thought to be due to accumulated oxidative damage) at an earlier age than small dogs (75), as well as the finding that dogs fed an energetically restricted diet tend to live longer than dogs fed a regular diet (38,43).…”
Section: Reduced Lifespan In Giant Breedssupporting
confidence: 66%
“…This damage is thought to remain latent for some time, but eventually results in an earlier onset of aging and degenerative disease as well as increased rates of certain cancers. This theory is supported by the finding that adult giant breed dog cells have a lower proliferative capacity than those of other breeds (45), that large dogs tend to develop nonhereditary cataracts (thought to be due to accumulated oxidative damage) at an earlier age than small dogs (75), as well as the finding that dogs fed an energetically restricted diet tend to live longer than dogs fed a regular diet (38,43).…”
Section: Reduced Lifespan In Giant Breedssupporting
confidence: 66%
“…Metabolic derangements also arise (14)(15)(16)(17) , and there are alterations in renal function (18) . All in all, obesity adversely affects quality of life (19) , and shortens lifespan (20) . Given these adverse effects on health and quality of life, canine obesity presents a major welfare challenge for veterinary surgeons.…”
Section: The Significance Of Obesity In Petsmentioning
confidence: 99%
“…For example, dogs fed a regular diet demonstrated greater radiographic severity of OA in the elbow in comparison to CR dogs after 6 years of diet treatment, but at year 8 (end of life mark), OA severity of both groups was not statistically different (Huck et al 2009). Similarly, a study that examined dogs with and without diet intervention for an entire lifespan found that there was only a 9 % decrease in OA incidence in the CR group (Kealy et al 2002). These findings indicate that CR may delay the onset of symptoms or radiographic evidence of OA but may not ultimately prevent the development of OA (Kealy et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a study that examined dogs with and without diet intervention for an entire lifespan found that there was only a 9 % decrease in OA incidence in the CR group (Kealy et al 2002). These findings indicate that CR may delay the onset of symptoms or radiographic evidence of OA but may not ultimately prevent the development of OA (Kealy et al 2002).…”
Section: Discussionmentioning
confidence: 99%